The Impact of Social Media on the Patients' Loyalty at Healthcare Services: A Field Study of Outpatient Departments at Sana'a Private Hospitals - Al-Towaity, Alia Mater Qaid Mohammed (University of Science and Technology, Sana'a, 2020)
Healthcare is an important part within countries economy, it was considered as a major resource in human and country development. Recently, the current situation in Yemen has caused a deterioration in providing healthcare services, which in role creating an urgent need for health facilities to adopt useful and suitable strategies. This would be helpful in providing and enhancing healthcare services‟ outcomes. Therefore, this study considered the previous studies concentration of the information exchange process between physician and patient, as well the process role of reinforce patients' trust by the reliable health information exchange through social network.. The study aimed at evaluating and suggesting a model that investigates the impact of social media on patients' loyalty at healthcare services in the outpatient departments at Sana'a private hospitals. This model examined the value of physicians' information communication behavior through social media, as one of the most post-care services‟ behaviors in need. The study followed the quantitative approach using a hand-delivered questionnaire distributed to a random sample of 187 individuals at their hospitals to prove the hypotheses of the model. The findings proved the usefulness of the model and supported its suggested development,its‟ showed the positive impact of social media on patients' loyalty at healthcare services by enhancing physicians' ICBs, which in turn leading to positive attitudes and behaviors of patients to be loyal and sustain with the same physicians.
Keywords: Social Media; Patients' Loyalty; Healthcare Services; Outpatient Departments; Sana'a Private Hospitals